HEGEMONI DALAM NOVEL SIXTH ANGEL KARYA LUNA TORASHYNGU: KAJIAN HEGEMONI GRAMSCI - Irma Hildayati; Titik Indarti; Resdianto Permata Raharjo (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
Hegemony is power or power used by a person or group of people to influence others. The hegemonic study used to analyze this literary work is Gramsci's hegemony. This study discusses the hegemony in the novel Sixth Angel by Luna Torashyngu. Qualitative approach is used. The method used in this study is in this study. namely descriptive method. The data source used is a literary work in the form of a novel entitled Sixth Angel by Luna Torasyngu. Data collection techniques used are 1) library techniques; 2) listen; and 3) note. The data analysis techniques used, 1) identification of short stories; 2) classifying data related to the theory of hegemony; 3) analysis of data related to the theory of hegemony; and 4) the presentation of the data in the novel. The purpose of this study is to identify and examine the theory of hegemony in the novel Sixth Angel by Luna Torasyngu. The results show that ideological hegemony and power have been found, including 1) ideological hegemony in Luna Torashyngu's novel Sixth Angel, including a) Ferdi hegemony meeting participants to form a joint special operation from various elements of the TNI; and b) Rachel hegemonized the helicopter technician to allow her to dive; and c) Doctor Hawagiri hegemonized Jason in search of genoid DNA; 2) the hegemony of power in Luna Torashyngu's novel Sixth Angel, including a) Muri hegemony Ista to collect data about fairy masks; b) The commander of Densus 88 hegemonized a company of his troops to surround the target's house; c) Major General Lily hegemonized Andra to tell Ferdi to immediately conduct an investigation; and d) Jason hegemonized the entire unit to catch fugitives. Keywords: hegemony, Gamsci, Sixth Angel